Policy windows and livelihood futures prospects for poverty reduction in rural India - Deshingkar Priya; Farrington John; Johnson Craig; Start Daniel (Oxford OUP, 2006)
The volume covers four major themes: managing tourism destinations and the determinants of travel choice; planning and policy making; development and evolution; and the impacts of tourism management on the society and the environment. In his scholarly in
Keywords: India; Manpower policy; Poverty; Rural-urban migration